Stocks are special too: an analysis of the equity lending market - Geczy, Christopher C.; Musto, David K.; Reed, Adam V. (Journal of Financial Economics, 2002)
With a year of equity loans by a major lender, we measure the effect of actual short-selling costs and constraints on trading strategies that involve short-selling. We find the loans of initial public offering (IPOs), DotCom, large-cap, growth and low-momentum stocks to be cheap relative to the strategies’ documented profits and that investors who can short only stocks that are cheap and easy to borrow can enjoy at least some of the profits of unconstrained investors. Most IPOs are loaned on their first settlement days and throughout their first months, and the underperformance around lockup expiration is significant even for the IPOs that are cheap and easy to borrow. The effect of short-selling frictions appears strongest in merger arbitrage. Acquirers’ stock is expensive to borrow, especially when the acquirer is small, though the major influence on trading profits is not through expense but availability.